An Antioxidant and Toxicity Test as Anticancer of Jewawut Extract (Setaria italica L.) Local Varieties of West Sulawesi - Tahar, Musrifah; Wahid, Masyitha; Hakim, Sufyan (Hasanuddin University, 2024)
Jewawut (Setaria italica L.) is a local plant that is widely found and consumed by the people of West Sulawesi. This cereal plant has various benefits, one of which is as an anticancer. So this study aims to determine the antioxidant and anticancer potential of methanol extract of Jewawut (Setaria italica L.). This research includes phytochemical test of secondary metabolites, antioxidant activity test with 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and identification of anticancer potential based on toxicity test with Brine Shrimp Lethality Test (BSLT) method. The results showed that the methanol extract of Jewawut (Setaria italica L.) contained secondary metabolite compounds including alkaloids, flavonoids, tannins, saponins, steroids and terpenoids. The extract has very weak antioxidant activity with an IC50 value of 4104.63 ppm and has potential as an anticancer with a toxicity value (LC50) of 41.65 μg/mL which means the toxicity is very strong.